Can the facts of UK inflation persistence be explainded by nominal rigidity - David Meenagh; Patrick Minford; Eric Nowell; Prakriti Sofat; Naveen Srinivasan (Cardiff University, Cardiff Business School, 2008)
It has been widely argued that inflation persistence since WWII has been widespread and durable and that it can only be accounted for by models with a high degree of nominal rigidity. We examine UK post-war data where after confirming previous studies findings of varying persistence due to changing monetary regimes, we find that models with little nominal rigidity are best equipped to explain it.
Keywords: E31; E37; 330; inflation persistence; New Keynesian; New Classical; nominal rigidity; monetary regime shifts; Inflation; Dauer; Geldpolitik; Preisrigidität; Großbritannien